Effects of workplace variables on the organizational commitment of Nigerian correctional staff. Issue 2 (3rd April 2021) - Lambert, Eric G.; Otu, Smart E.; Elechi, O. Oko
ABSTRACT: Organisational commitment is an important concept in the field of corrections. The current study examined how workplace variables affected commitment among Nigerian correctional staff and compared the results to the findings of past studies of U.S. correctional staff. Specifically, the effects of the workplace variables of input into decision-making, quality training, job variety, quality supervision, perceived dangerousness of the job, and role overload were examined. Input, quality training, job variety, and quality supervision had significant positive effects on commitment. Dangerousness and overload had nonsignificant effects. As with past U.S. studies, the current findings indicate commitment to the organisation is stronger when staff are treated in a positive manner.